Effect of Fermented Cassava Peel with Bacillus amyloliquefaciens in the Diet on the Performance of Indigenous Chicken - Friedric, Julian D.; Mirzah, Mirzah; Wizna, Wizna; Yano, Aan A. (Syiah Kuala University, 2025)
Feed cost is a major challenge in poultry production, prompting the need for alternative feed resources to reduce dependency on conventional ingredients. Cassava peel, an abundant agro-industrial by-product, offers potential as a feed ingredient. This study aimed to determine the effect of fermented cassava peel (FCP) flour using Bacillus amyloliquefaciens on the growth performance of indigenous chickens. A total of 100 day old chicks were allocated to five dietary treatments with four replications in a completely randomized design (CRD): Control (T0) (0% FCP), T1 (15% FCP), T2 (20% FCP), T3 (25% FCP), and T4 (30% FCP). Data on feed intake (FI), body weight gain (BWG), and feed conversion ratio (FCR) were collected over eight weeks and analyzed using one-way ANOVA followed by Duncans Multiple Range Test at 5% significance. Results show that the inclusion of FCP up 40% had no significant effect (P0.05) on FI, BWG, and FCR. These findings indicate that FCP flour can replace conventional feed ingredients in indigenous chicken without compromising growth performances. Further research is recommended to optimize feed formulation by balancing nutrient content and selecting effective fermenting microorganisms to fully harness the benefit of FCP in poultry production systems.